The presence of periopathogenic bacteria in subgingival and atherosclerotic plaques – An age related comparative analysis - Ibrahim Kannosh; Danijela Staletovic; Bosko Toljic; Milena Radunovic; Ana Pucar; Sanja Matic Petrovic; Ivana Grubisa; Milos Lazarevic; Zlata Brkic; Jelena Knezevic Vukcevic; Jelena Milasin (Journal of Infection in Developing Countries)
Introduction: There is a known connection between periodontitis and atherosclerosis and the presence of periopathogens in blood vessels. However, changes of the oral microflora related to the aging process and its possible effects on atherosclerosis, have yet to be analyzed. The aim of this study was to assess temporal changes in the frequency of periodontal bacteria in the subgingival plaque and in atherosclerotic blood vessels of patients with atherosclerosis.